Pengaruh Compensation Satisfaction dan Supervisory Support Terhadap Engagement Karyawan (Studi Pada Karyawan Perusahaan Manufaktur di Provinsi Banten). - Nafiudin Nafiudin; Andari (Universitas Serang Raya, 2022)
Employee engagement in Indonesia is still relatively low at 13%, the low level of employee engagement has an impact on many things such as employee performance, therefore special attention is needed so that companies are able to increase employee engagement, and than This research intended to find out effectof Compensation Satisfaction and Supervisory Support on the employee engagement in Banten. This study uses a quantitative method with an associative descriptive design, research data collected using questionnaires and data analys is using multiple linear withthe SPSS IBM 20. program and based on the resulst of hypothesis testing both partially and simultaneously, it is obtained that Compensation Satisfaction and Supervisor Support have an influence on Employee Engagement in manufacturing at Banten. With a total contribution of the R2 valueof 0.240. Keywords: Supervisor Support; Employee Engagement; Compensation Satisfaction